2013
DOI: 10.1248/bpb.b13-00021
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin Attenuates Acute Myocardial Infarction of Rats <i>via</i> Mediating the Mitogen-Activated Protein Kinase Pathway

Abstract: Baicalin is a bioactive ingredient from the herb and has possessed various pharmacological actions. The present study was performed to evaluate the cardioprotective potential of baicalin against myocardial infarction and explore the potential mechanism. Baicalin was intraperitoneally injected into the rats by the doses of 50, 100 and 200 mg/kg, respectively, once a day for 7 d and, 30 min after the last administration, the left coronary artery was ligated. Infarct size was measured to analyze the myocardial da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 31 publications
(39 reference statements)
3
28
0
1
Order By: Relevance
“…Several groups reported that baicalin induced apoptosis of cancer cells [46] and carcinoma cells [47], via ERK and p38 MAPK signaling pathways. However, baicalin also showed cytoprotective effects on CMs [48,49], hepatocytes and neural cells [50,51,52]. A latest study reported that baicalin attenuates acute myocardial infarction of rats via mediating ERK and p38 MAPK signaling pathways [48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several groups reported that baicalin induced apoptosis of cancer cells [46] and carcinoma cells [47], via ERK and p38 MAPK signaling pathways. However, baicalin also showed cytoprotective effects on CMs [48,49], hepatocytes and neural cells [50,51,52]. A latest study reported that baicalin attenuates acute myocardial infarction of rats via mediating ERK and p38 MAPK signaling pathways [48].…”
Section: Discussionmentioning
confidence: 99%
“…However, baicalin also showed cytoprotective effects on CMs [48,49], hepatocytes and neural cells [50,51,52]. A latest study reported that baicalin attenuates acute myocardial infarction of rats via mediating ERK and p38 MAPK signaling pathways [48]. In this latest study, baicalin treatment significantly augments the phosphorylated ERK (p-ERK) while dramatically diminishes the phosphorylated JNK (p-JNK) and p38 (p-p38) in rats with myocardial infarction [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baicalein (BAI) , which is involved in oxidative stress, inflammation, tumorigenesis, and angiogenesisis, is the main component of the Chinese traditional drug "Huang Qin", (Gao et al, 1999). It has been reported that BAI remarkably retards is chemia/reperfusion-induced myocardium injury (Liu et al, 2013;Wang et al, 2013). However, its exact mechanism remains elusive and its role in AAA development has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…43 In this study, cardiac protective effects of Sch B loaded SLNs were evaluated using an acute MI model. MMP-Sch B SLNs …”
mentioning
confidence: 99%